Prognostic impact of CD5 expression in diffuse large B‐cell lymphoma in patients treated with rituximab‐EPOCH. (30th January 2017) - Thakral, Beenu; Medeiros, L. Jeffrey; Desai, Parth; Lin, Pei; Yin, C. Cameron; Tang, Guilin; Khoury, Joseph D.; Hu, Shimin; Xu, Jie; Loghavi, Sanam; Hu, Bei; Oki, Yasuhiro; et al.
Abstract: Objectives: CD5‐positive (CD5+) diffuse large B‐cell lymphoma (DLBCL) represents 5%‐10% of all DLBCL cases, which has been associated with a poorer prognosis in patients treated with R‐CHOP. Prognostic impact of CD5 expression in patients with DLBCL treated with R‐EPOCH has not been evaluated. Methods: We studied 130 patients with de novo DLBCL who received frontline R‐EPOCH therapy. The clinicopathologic features and overall survival (OS) were compared between patients with CD5+ and CD5‐ DLBCL. MYC, BCL2, and BCL6 rearrangements were examined by fluorescent in situ hybridization. Results: Sixteen (12.3%) of 130 DLBCLs were CD5+. Most clinicopathologic features including cell of origin and frequency of MYC, BCL2, and BCL6 rearrangements were similar between CD5+ and CD5− groups. Patients with CD5+ DLBCL, however, showed higher rate of central nervous system relapse (33.3% vs 15.6%; P <.01) and a higher Ki67 proliferative index compared with CD5‐ patients. The median OS was significantly worse in CD5+ than CD5‐ patients (28.13 months vs not reached, P =.006). CD5 expression was an independent prognostic factor for OS in multivariate analysis. Conclusions: R‐EPOCH therapy does not seem to impact the known poorer prognosis of patients with de novo CD5+ DLBCL, and CD5 expression was still an independent prognostic factor in R‐EPOCH‐treated patients with DLBCL.